(untitled) (Research, Society and Development, 2023)
Introduction: the COVID-19 Pandemic deeply has affected the structure of society in all spheres. The peculiarities of dental services, placed these in the centre of attention. This review article aimed to raise the main scientific evidence that guided the practices and organization for the provision of dental services. Methodology: this is a review study for the synthesis of evidence, involving studies developed since January 2020 and October 2022. Results: 102 articles were selected for analysis, having evidenced that the pandemic deeply affected dental services. Its impacts consisted in the reduction of the supply of services, challenges of adopting stricter biosafety protocols. Dental professionals were required to reinvent themselves for a new reality in their clinical practices; deal with the fear and anxiety of getting infected and infecting their families; and by the uncertainties of financial sustainability to keep the offices functional. Drug prescriptions and a tele-dentistry were the major alternative for offering the services. Concluding remarks: the lessons from the experience with the pandemic, will be part of the future of the post-pandemic, as well as of clinical practice and management of dental services.